Spatial Distribution Characteristics and Influencing Factors of Geographical Indication Agricultural Products in Shaanxi Province - Zhu, Chunyu (International Journal of Global Economics and Management, 2024)
Geographical indication agricultural products are of great significance to promote the high-quality development of rural revitalization due to their unique quality and brand value. Based on the geographical concentration index, the nearest neighbor index and the kernel density estimation method, this paper empirically studies the spatial distribution characteristics and influencing factors of 117 geographical indication agricultural products in Shaanxi Province. The results show that the spatial distribution of geographical indications in Shaanxi is extremely uneven, showing the characteristics of ’ dense in the south and sparse in the north, regional agglomeration ’. From the perspective of density distribution characteristics, the overall spatial distribution of geographical indications in Shaanxi shows a distribution pattern of ’ three high and three times ’, and the three high-density areas show a agglomeration distribution pattern of ’ pin-shaped ’. The difference between the north and the south is obvious, and the overall distribution pattern is ’ cold in the north and hot in the south ’. The spatial distribution pattern of geographical indications in Shaanxi is affected by many factors. Natural factors are the basis, social and economic factors strengthen the spatial distribution pattern of geographical indications, and government-led and policy factors play a regulatory and guiding role. It is suggested to optimize the spatial distribution pattern of geographical indications in Shaanxi, rely on local social resources, give full play to the leading role of the government, and actively promote the industrialization development of geographical indication products.